Plastic & health: the hidden costs of a plastic planet (Geneva, 2019)
"Despite being one of the most pervasive materials on the planet, plastic and its impact on human health is poorly understood. Human exposure to it grows with increasing plastic production and use. Research into the human health impacts of plastic to date have focused narrowly on specific moments in the plastic lifecycle, from wellhead to refinery, from store shelves to human bodies, and from disposal to ongoing impacts as air pollutants and ocean plastic. Individually, each stage of the plastic lifecycle poses significant risks to human health. Together, the lifecycle impacts of plastic paint an unequivocally toxic picture: plastic threatens human health on a global scale."